Analisis Makna Pasal 34 Ayat 1 UUD 1945 dan Implikasinya Terhadap Jaminan Kesejahteraan Warganegara Indonesia - Najwa, Atika; Adisty, Muhammad Luthfi Fauzi Putra; Anbiya, Bakhti Fatwa (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The 1945 Constitution is the constitution and is the highest source of law for the unitary state of the Republic of Indonesia. The existence of the 1945 Constitution aims to protect and prosper the nation. Article 34 Paragraph 1 of the 1945 Constitution regulates the state's responsibility towards the poor and abandoned children, emphasizes the need for the government and society as a whole to act to ensure the welfare of children, aims to guarantee their welfare and protection, and emphasizes the importance of government and community participation in achieving the goal. Despite this, reality still shows that there are many neglected children in Indonesia, who face physical, psychological and social challenges. Neglected children are defined as children who do not have adequate protection and care, while the poor are those who live in extreme poverty without access to basic needs. While the constitution emphasizes protection and welfare for these groups, there are still many challenges in implementation. These problems are not only social in nature but also involve economic, political, cultural, educational, and legal aspects, thus requiring the active role of the government and multisectoral cooperation. This research uses documentation and literature review methods, as well as reviewing various related journals to evaluate the enforcement of the rights of the poor and abandoned children contained in article 34 paragraph 1.